The Curious Case of Aleksandar Milivojević: The Donja Toponica Hospital and Mental Health in Socialist Yugoslavia. (23rd June 2019) - Simic, Ivan
Summary: This article uncovers the appalling situation in Yugoslav mental hospitals in the early period of Yugoslav socialism, demonstrating that Yugoslav psychiatry suffered from rife structural problems and malpractices. By examining the case of the Toponica hospital, the article shows that patients were regularly abused and beaten while living in very harsh conditions. Patients were overmedicated, therapies administered by illiterate staff, medical histories poorly recorded and hospitals overcrowded and understaffed, while often no attempts were made for the patients' healing and rehabilitation. On the other hand, Yugoslav psychiatrists closely followed the trends in global psychiatry, testing new therapies, while the movement for mental hygiene gained significant traction. Nevertheless, high hopes for improving the patients' well-being were far from practice. Once the scandal at the Toponica hospital erupted in 1955, it caused changes in the management and brought in more resources, but the structural problems of Yugoslav psychiatry remained.